2009
DOI: 10.1002/jnr.22288
|View full text |Cite
|
Sign up to set email alerts
|

Promoting directional axon growth from neural progenitors grafted into the injured spinal cord

Abstract: Spinal cord injury (SCI) is a devastating condition characterized by disruption of axonal connections, failure of axonal regeneration, and loss of motor and sensory function. The therapeutic promise of neural stem cells has been focused on cell replacement but many obstacles remain in getting neuronal integration following transplantation into the injured CNS. In this study we investigated the neurotransmitter identity and axonal growth potential of neural progenitors following grafting into adult rats with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 40 publications
1
92
0
1
Order By: Relevance
“…Our present data support the potential for grafted hiPSC-NSs to form synapses with host neurons in the injured spinal cord. Previous studies have shown post-SCI functional improvements associated with intraspinal grafts containing neuronal progenitors either alone or in combination with other cells or interventions (4,7,(39)(40)(41)(42)(43). Such studies also report that graft-derived human neurons can receive projections from host mouse neurons and that their extended processes make synapses with host neurons (39).…”
Section: Discussionmentioning
confidence: 96%
“…Our present data support the potential for grafted hiPSC-NSs to form synapses with host neurons in the injured spinal cord. Previous studies have shown post-SCI functional improvements associated with intraspinal grafts containing neuronal progenitors either alone or in combination with other cells or interventions (4,7,(39)(40)(41)(42)(43). Such studies also report that graft-derived human neurons can receive projections from host mouse neurons and that their extended processes make synapses with host neurons (39).…”
Section: Discussionmentioning
confidence: 96%
“…Local application of recombinant GDNF, a member of the transforming growth factor beta family induced rescue of the injured motoneurons and satisfactory reinnervation of the target muscle when applied in co-treatment with riluzole (Bergerot et al 2004). Other strategies involved the use of progenitor and stem cells in the vicinity of the reimplanted ventral root (Hell et al 2009, Su et al 2009, Bonner et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However, these effects were investigated in a peripheral nerve lesion model (lumbar rhizotomy and excitotoxic root lesion), not in a SCI model. E13.5 rat spinal cord-derived NRPs/GRPs differentiated into GABAergic and glutamatergic neurons after grafting into a rat spinal cord lesion model (dorsal column transection) (Bonner et al 2010 ). Axonal outgrowth over a limited distance into the host spinal cord from these neurons was promoted by injection of a lentiviral vector expressing the neurotrophic factor BDNF.…”
Section: Neuronal Replacementmentioning
confidence: 99%